Perencanaan Stratejik Sistem Informasi dan Proses Pembelajarannya di Organisasi - Dekar Urumsah (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2005)
Planning a strategy, implementing an information technology, and running organizational learning process have become the most important things in an organization. There are many organizations have devel¬oped a strategic approach by planning its IS/IT. Planning IS/IT is complicated and important since there many factors effecting the planning of IS/IT. They are the types of planning, the relationship between strategy, IS, and IT, the methodology of IT strategy, and the portfolio of IS/IT.The implementation of IS/IT is a complex effort because IS/IT evolves in a set of technology continuously. Individuals in the organization will adapt to the evolving IS/IT, where they learn new ways in con¬ducting their tasks. This process of learning involves the previous procedures, which are changed into a new pat¬tern to strengthen the process itself. It has become individual and group procedures. It is covering all aspects but it can be summarized in four phases. They are investment and technology identification, the adaptation and tech¬nology learning, the management control, and the technology transfer.